Education With Video on Diabetes Mellitus Patients' Treatment Compliance Based on The Philosophy of Ontology: A Review - Hentu, Ardin S; Worang, Triska Yolanda; Tairas, Jean Siska Roma (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background : Diabetes Mellitus is a metabolic disorder in which the body is unable to produce insulin or cannot maximize the work of insulin produced by the pancreas. Objective: This literature aims to analyze the philosophical study from the perspective of Ontology. Article searches come from several sources such as ProQuest, Google Scholar, PubMed, and other search engines using the keywords education in diabetic patients” Or “diabetic patient video education” and “diabetes management education using video”. Results: obtained from the literature search found that providing video-based education can improve medication compliance in diabetes mellitus patients. Conclusion: video-based education can be applied to diabetes mellitus patients and can be applied in one of the nursing care interventions.